An Open-Label Pilot Study of Duloxetine in Patients With Irritable Bowel Syndrome and Comorbid Major Depressive Disorder. Issue 6 (December 2016) - Lewis-Fernández, Roberto; Lam, Peter; Lucak, Susan; Galfalvy, Hanga; Jackson, Elizabeth; Fried, Jane; Rosario, Melissa; de la Cruz, Ana Alicia; Sánchez-Lacay, Arturo; Díaz, Samantha; Schneier, Franklin
Abstract : Abstract: Major depressive disorder (MDD) and irritable bowel syndrome (IBS) frequently co-occur, yet treating their comorbid presentation is challenging. Low-dose tricyclic antidepressants are efficacious for IBS, but higher doses to treat depressive symptoms present tolerability problems, whereas selective serotonin reuptake inhibitors are more tolerable but show inconsistent efficacy for IBS. If efficacious, serotonin-norepinephrine reuptake inhibitors like duloxetine would provide a useful alternative. We explored efficacy, tolerability, and time to onset of action of duloxetine in comorbid IBS-MDD in an open-label, 12-week trial. Repeated-measures mixed-effects regression analysis with the intent-to-treat sample assessed rate of change of the clinician-administered Gastrointestinal Symptoms Rating Scale, Montgomery-Åsberg Depression Rating Scale, and other clinician-administered and self-report scales. Seventeen Hispanic adults with current MDD and comorbid IBS meeting Rome III criteria entered the study. Medical and laboratory assessment ruled out alarm symptoms and signs inconsistent with IBS. Duloxetine led to significant improvement in Gastrointestinal Symptoms Rating Scale and Montgomery-Åsberg Depression Rating Scale scores and 71.4% and 64.3% intent-to-treat response rates for IBS and MDD, respectively. Abdominal pain severity decreased by 56%. Contrary to expectation of rapid analgesic effects, based on duloxetine studies for neuropathic pain, both IBS and MDD symptoms improved gradually; differences in slopes of improvement were nonsignificant. Duloxetine was moderately well tolerated at a mean endpoint dose of 60 mg/d. Study limitations include the lack of placebo control, modest sample size, single ethnic group, and high attrition rate. Duloxetine efficacy for comorbid IBS-MDD should be studied under placebo-controlled conditions with larger and more diverse samples.